Development of a Secondary SCRAM System for Fast Reactors and ADS Systems - Simon Vanmaercke; Gert Van den Eynde; Engelbert Tijskens; Yann Bartosiewicz (Science and Technology of Nuclear Installations)
One important safety aspect of any reactor is the ability to shutdown the reactor. A shutdown in an ADS can be done by stopping the accelerator or by lowering the multiplication factor of the reactor and thus by inserting negative reactivity. In current designs of liquid-metal-cooled GEN IV and ADS reactors reactivity insertion is based on absorber rods. Although these rod-based systems are duplicated to provide redundancy, they all have a common failure mode as a consequence of their identical operating mechanism, possible causes being a largely deformed core or blockage of the rod guidance channel. In this paper an overview of existing solutions for a complementary shut down system is given and a new concept is proposed. A tube is divided into two sections by means of aluminum seal. In the upper region, above the active core, spherical neutron-absorbing boron carbide particles are placed. In case of overpower and loss of coolant transients, the seal will melt. The absorber balls are then no longer supported and fall down into the active core region inserting a large negative reactivity. This system, which is not rod based, is under investigation, and its feasibility is verified both by experiments and simulations.